Atenção à saúde da população em situação de rua: reflexões sobre possibilidades da educação física no consultório na rua - Rios, Gleyson Batista (2023)
This is a bibliographical research with the objective of identifying directions for the professional performance of Physical Education in the Consultório na Rua. The research was developed in two stages. The first stage was a Literature Review with the aim of identifying and analysing theses, dissertations and articles on Consultório na Rua that are related to Physical Education. The texts were selected from the Digital Library of Theses and Dissertations (DLTD), in August 2021 and from the Journal CAPES database, in January 2022. The initial results pointed to an inexpressive presence of Physical Education in research involving the Consultório na Rua. Based on this result, the second stage was outlined in order to find theoretical subsidies that could contribute to Physical Education in the Consultório na Rua. At this stage, a data triangulation was carried out from the analysis of documents comprising the official guidelines for the Street Clinic, the scientific production that discusses Physical Education in primary care and mental health and elements of the author's experience, referring to the period in which he worked as a Physical Education professional in a Consultório na Rua team. After this path, we identified the reinforcement of the need for intersectoral and intrasectoral articulation for the whole care of the homeless population. There is also an indication that the diversification of body practices is presented as an important element for the organization of the work process, aiming at greater adherence, and that the differences in the socio-historical debate linked to body practice and physical activity are not trivial, but fundamental for articulating the clinical and political dimensions of the Consultório na Rua.